2017
DOI: 10.1210/jc.2017-00272
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy-Associated Plasma Protein A Concentrations Are Associated With Third Trimester Insulin Sensitivity

Abstract: Context:First or early second trimester pregnancy-associated plasma protein A (PAPP-A) concentrations have previously been shown to be lower in women who subsequently develop gestational diabetes mellitus (GDM) and gestational hypertension.Objective:We therefore sought to investigate why circulating PAPP-A concentrations are related to the subsequent risk of GDM and gestational hypertension.Patients, Design, and Setting:We measured serum PAPP-A concentrations around week 15 of pregnancy and related these to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…On the other hand, PAPP‐A was downregulated in GDM exosomes compared with exosomes from NGT. Low levels of circulating PAPP‐A in maternal plasma has been associated with GDM and high levels of CAMK2 in skeletal muscle from GDM have been associated with decrease in insulin sensitive . Therefore, PAPP‐A and CAMK2β were chosen for the validation of the proteomic data in an independent cohort of women with NGT and GDM using ELISA kits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, PAPP‐A was downregulated in GDM exosomes compared with exosomes from NGT. Low levels of circulating PAPP‐A in maternal plasma has been associated with GDM and high levels of CAMK2 in skeletal muscle from GDM have been associated with decrease in insulin sensitive . Therefore, PAPP‐A and CAMK2β were chosen for the validation of the proteomic data in an independent cohort of women with NGT and GDM using ELISA kits.…”
Section: Resultsmentioning
confidence: 99%
“…Low maternal circulating concentrations of PAPP‐A is correlated with adverse pregnancy outcomes including GDM . Notably, PAPP‐A levels in the first trimester is associated with insulin resistance later in pregnancy . Likewise, in this study, we found that PAPP‐A expression is lower in GDM exosomes compared to NGT exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…At a median (inter-quartile range) of 28.4 (28.1-28.7) weeks gestation 1,074 of the CBGS mothers underwent a 75g oral glucose tolerance test (OGTT) after fasting overnight. 27 Venous blood was collected just prior to and 60 min. after the glucose load was administered for the measurement of plasma glucose, insulin and c-peptide concentrations.…”
Section: Oral Glucose Tolerance Test and Gestational Diabetes Diagnosmentioning
confidence: 99%
“…The prospective Cambridge Baby Growth Study recruited 2,229 mothers (and their partners and offspring) attending antenatal ultrasound clinics during early pregnancy at the Rosie Maternity Hospital, Cambridge, United Kingdom, between 2001 and 2009 [17]. All mothers were over 16 years of age.…”
Section: Cohortmentioning
confidence: 99%